Outside Cover Picture: Plasma Process. Polym. 7/2020. Issue 7 (3rd July 2020) - Zhang, Jishen; Liu, Dingxin; Zhang, Hao; Xia, Wenjie; Liu, Yifan; Sun, Bowen; Xu, Dehui; Guo, Li; Kong, Michael G.
Abstract : Outside Front Cover : The anticancer eff ects of a plasma jet on 3D multicellular tumor spheroids with or without liquid coverage were examined. It was found that cell viability decreased more rapidly without liquid coverage than with liquid coverage. The distribution of apoptotic cells and ROS were closely related to the location of the plasma‐irradiated spot (liquid or spheroids). Importantly, liquid can help ROS penetrate into spheroids and prolong the anticancer eff ects of plasma. Further details can be found in the article by Jishen Zhang, Dingxin Liu, Hao Zhang, et al. (e1900213 ).